Health Related Quality of Life of Pregnant Women Attending Antenatal Clinic of a Tertiary Level Hospital - Paudel, Radha; Deuja, Anisha (Europasian Journal of Medical Sciences, 2021)
Background: Pregnancy is a normal physiological process; the major changes at that period are related to the direct impact on health-related quality of life. The main objective of the study was to assess the health-related quality of life of pregnant women. Methods: A descriptive cross-sectional study design was used among 106 pregnant women. A non-probability purposive sampling technique was used. Data were collected from 23 August 2019, to 31 August 2019. A semi-structured interview schedule was used for data collection. Data were analyzed by using descriptive statistical methods such as frequency, percentage, mean, standard deviation, and inferential statistics such as Chi-square test and Fischer’s exact test was used to associate selected socio-demographic and obstetric characteristics with the level of quality of life. A p value less than 0.05 was used for statistical significance. Result: The study showed that the respondent’s level of health related quality of life was highest in the psychological domain 102 (96.2%) and the lowest level 15 (14.2%) was found in the physical domain. There was a significant association of physical domain in health related quality of life with the age of pregnant women (p-0.003) while the type of family, parity, mode of delivery, and duration of pregnancy was not associated with the physical, psychological, and social domain at p <0.05. Conclusion: The health related quality of life of pregnant women, in general, was good. The physical domain was most affected than the psychological and social domain. The level of health related quality of life of the pregnant women in the physical domain is associated with the age of pregnant women. Improving the quality of life of pregnant women requires better identification of their difficulties and guides them from midwives since early pregnancy whenever possible.